INTEROBSERVER RELIABILITYOF NEW DIABETIC FOOT ULCER SCALE IN INDONESIA: A CROSS SECTIONAL BASED PICTURES STUDY - Muhtar, Trini Andini; Sari, Mutmainnah; Yusuf, Saldy (ETN Centre Indonesia, 2018)
Background: Recently, Diabetic Foot Ulcer Assessment Scale (DFUAS) has been developed based on the characteristic of Diabetic Foot Ulcers (DFU) in Indonesia. DFUAS consist of 11 sub scales and its validity reported adequately. However, the reliability of DFUAS has not investigated. Therefore, application of DFUAS in clinical setting remains unclear. Objective: The aim of the current study was to evaluate interobserver reliability of DFUAS. Method: This was a cross sectional study, conducted in RUMAT (Rumah Perawatan) with the eligibility criteria of the observer as Wound Care Nurses. DFU?s status was scored using DFUAS based on 10 various pictures (Wagner I, II, III, IV and V) from Griya Afiat database. Interobserver reliability was calculated using Cronbach Alpha for each sub scales (SPSS 16.0). Results: Current study involved 44 wound care nurses (11 males, 32 females), nursing education background (vocational: 10 nurses, professional: 34 nurses) with experience as a wound care nurse (< 2 year, 31 nurses) and (> 2 years 11 nurses). Interobserver agreement confirmed by Cronbach Alpha for each sub scale, including depth (0.509), inflammation/infection (0.690), maceration (0.628), type of necrotic tissue (0.296), the proportion of necrotic tissue (0.530), the proportion of slough (0.467), the proportion of granulation (0.560), size (0.627), size score (0.177), tunneling (0.759) and type of wound edge (0.400). Overall Cronbach Alpha was 0.654. Conclusions: This study confirmed moderate reliability of DFUAS among different wound care nurse in Indonesia. Training how to use DFUAS is essential to increase its reliability.